Victory of Non-Elite Candidates in Electoral Contestations: An Analysis of Tibrani's Elections in The 2024 Legislative Election - Ardiansah, Ardiansah; Aidinil, Aidinil Zetra; Roni, Roni Ekha Putera (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
This study analyzes the political strategy of Tibrani, a non-elite cadre of the National Awakening Party (PKB), in winning the 2024 Legislative Election in Tengah Ilir Subdistrict, Tebo Regency, Jambi Province. The case contests the notion that economic capital and elite status alone determine political victory. Using a qualitative approach with an intrinsic case study design and an explanatory method, data were collected through in-depth interviews, participatory observations, and documentation. Findings reveal that Tibrani succeeded by engineering social capital, orchestrating social networks, and building a participatory ecosystem. His political communication emphasized narrative, multichannel messaging, and collective identity. The study concludes that non-elite actors can succeed electorally through participatory strategies and community-based approaches. This research contributes to the discourse on alternative political strategies in local democracy.